The Study of Turn Taking Created in “Cinderella” Movie 2015 - Rachma Nurma Gupita; Katharina Rustipa (Dinamika Bahasa dan Budaya, 2021)
This research has two objectives. The first objective is to find the type of turn-taking mechanism in the dialogue of David Barron's "Cindeella (2015)" film. the second objective is to find out what kind of turn-taking mechanism is mostly used in the dialogue of David Barron's "Cinderella (2015)" film. This research is descriptive research. The data of this research is the dialogue film "Cinderella (2015)" by David Barron. The research data is oral data containing turn-taking which includes a form of turn-taking mechanism in the dialogue "Cinderella (2015)" by David Barron. The data were obtained by using the listening method with the speech-free listening technique followed by recording, transcript, and note-taking technique. The validity of the data was done by using the author's observation. The result of this study is related to turn-taking as seen from the aspect of the turn-taking mechanism. The form of turn-taking mechanism in the dialogue of David Barron's film"Cinderella (2015)" found three turn-taking mechanism namely taking the floor, holding the floor, yielding the floor.